Factors associated with delayed patient appraisal of colorectal cancer symptoms - Siminoff, Laura (Psychooncology, 2014)
OBJECTIVE: To evaluate the relationship between symptoms, financial and cognitive barriers with patient delays in seeking evaluation of symptoms. METHODS: Data were collected from 252 colorectal cancer patients from academic and community oncology practices in Virginia and Ohio. We used a cross-sectional, mixed methods design collected data through patient interviews and medical record reviews. Structural equation modeling (SEM) tested the hypothesized relationships between symptoms, financial and cognitive barriers and patient care seeking delays. RESULTS: In bivariate analyses, patients who reported a financial barrier to accessing health care (t (246) = −2.6, p < 0.01) were more likely to have greater care-seeking delays. Model testing revealed that experiencing cognitive barriers was a significant, positive, direct predictor of appraisal delay (0.35; p < 0.01). Indirect pathways from symptoms (0.07; p < 0.05) and financial barriers (0.09; p < 0.05) to appraisal delay via cognitive barriers were significant. CONCLUSIONS: Patient interpretations of symptoms were influenced by financial barriers. Conceptualizing financial barriers as a component of the symptom appraisal process is conceptually different from viewing it as only a structural barrier preventing healthcare access.